Присвята з городища Беляус - Соломоник, Е.І. (Археологія, 1992)
Публікація присвячена унікальній знахідці 1989 р. Публикация посвящена уникальной находке 1989 г.— посвятительной надписи богине Гекате из городища Беляус. Плита, обнаруженная в скифской постройке І в. н. э., видимо, попала из греческих слоев городища. По характерным особенностям уверенно датируется ІІІ в. до н э. The paper deals with a unique finding of 1989 — the inscription to the goddess Hecate from the settlement Belyaus. The plate found in the Scythian construction of the 1st century AC had appeared there apparently from the Greek layers of the settlement. It is reliably dated to the 3d century BC by its peculiarities.